A Pastoral Counseling Model for Christian Generation Z Experiencing Future Anxiety - Susanna Kathryn; Anggia Hapsari; Ronny Taufik (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Christian Generation Z is negotiating adulthood within an unusually dense field of uncertainty: unstable work transitions, digital comparison, climate concern, post-pandemic disruption, and shifting religious participation. These conditions intensify future anxiety, understood here as anticipatory apprehension toward an unfavorable personal future. This article aims to construct a pastoral counseling model for Christian Gen Z who experience future anxiety without reducing their distress either to a clinical disorder alone or to insufficient faith. Because no field data were collected, the study uses a constructive conceptual design grounded in an integrative literature review, practical theological reasoning, and a critical synthesis of psychological, pastoral, and youth mental health scholarship published before 2024. The analysis identifies three main findings. First, future anxiety among Christian Gen Z is best interpreted as a narrative disruption of agency, meaning, belonging, and hope. Second, pastoral counseling requires an integrative stance that combines spiritual competence, evidence-informed anxiety care, digital awareness, and ecclesial accompaniment. Third, the article proposes the SELAH model: Situational-spiritual assessment, Empathic presence, Lament and meaning reconstruction, Adaptive agency planning, and Hope-building ecclesial accompaniment. The model offers a non-reductive framework for churches, counselors, and Christian educators while emphasizing referral, ethical boundaries, and further empirical testing.